(untitled) (Cardiovascular Journal, 2018)
Background: In coronary artery bypass surgery (CABG) left internal mammary artery (LIMA) is considered gold standard conduit of choice for myocardial revascularization. Graft failure following CABG reduces cardiac mortality and morbidity both in short and long term. Although conventional angiography is gold standard for assessing graft patency but rarely available in same operating room. So intraoperative florescence imaging could be an efficient and reliable method of assessing the patency of graft. Methods: This study was conducted between July 2013 to June 2014 in the Department of Cardiac Surgery of National Institute of Cardiovascular Diseases (NICVD). Thirty six LIMA grafts were assessed by using IFI system .ICG administered through CVP line and imaging acquired during pass of the ICG through field of view graft flow. Quality of anastomosis was intra operatively to validate graft. Results: Mean age of study population was 54±8.38 years. Per operative assessment of LIMA to left anterior descending artery revealed 32 (88.8%) patent anastomosis, narrowing of anastomosis was found in 2 (5.55% ) patients. Conclusion: Intraoperative fluorescence imaging is an effective and inexpensive way to validate patency of LIMA graft. Cardiovasc. j. 2018; 10(2): 145-149